The quick : a novel - Owen, Lauren, 1985- (New York : Random House, 2014)
London, 1893: James Norbury is a would-be poet, from Oxford and confounded by the city at his doorstep. Taking up lodging with a young aristocrat, he is introduced to the drawing rooms of high society and finds love in an unexpected quarter. On the cusp of achieving a happiness long denied to him, he vanishes without a trace. In Yorkshire, his sister Charlotte sets out to find her brother.
Keywords: Brothers and sisters -- Fiction; Private clubs -- Fiction; Vampires -- Fiction; London (England) -- Fiction; Mystery fiction; Suspense fiction